2017
DOI: 10.1016/j.ygyno.2017.05.016
|View full text |Cite
|
Sign up to set email alerts
|

A prospective validation study of sentinel lymph node mapping for high-risk endometrial cancer

Abstract: Objective Sentinel lymph node (SLN) mapping continues to evolve in the surgical staging of endometrial cancer (EC). The purpose of this trial was to identify the sensitivity, false negative rate (FNR) and FN predictive value (FNPV) of SLN compared to complete pelvic and para-aortic lymphadenectomy (LAD) in women with high-risk EC. Methods Women with high-risk EC (grade 3, serous, clear cell, carcinosarcoma) were enrolled in this prospective surgical trial. All patients underwent preoperative PET/CT and intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
149
4
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 190 publications
(169 citation statements)
references
References 27 publications
7
149
4
9
Order By: Relevance
“…5 Cancer October 1, 2019 If peritoneal disease was encountered during surgery, sentinel lymph node mapping and lymphadenectomy were performed at the discretion of the surgeon.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Cancer October 1, 2019 If peritoneal disease was encountered during surgery, sentinel lymph node mapping and lymphadenectomy were performed at the discretion of the surgeon.…”
Section: Methodsmentioning
confidence: 99%
“…This decision was based on prospective data published by the Gynecologic Oncology Group (GOG) that established a relationship between disease prognosis and surgically determined risk factors. 5,6 In an effort to predict extrauterine disease preoperatively and optimize surgical planning, a multitude of noninvasive techniques have been evaluated. Although complete lymphadenectomy is included in the FIGO staging of endometrial cancer, it remains controversial, especially in those patients with presumed early-stage disease.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of sentinel lymph node mapping to detect metastases is higher than 90%, reaching almost 100% in a meta‐analysis . Randomized studies have suggested that sentinel lymph node mapping can safely replace lymphadenectomy in the staging of endometrial cancer …”
Section: Is Lymphadenectomy Therapeutic?mentioning
confidence: 99%
“…The largest, dedicated clinical trial that has addressed this question was conducted by Soliman et al38 This single institution, prospective trial enrolled 101 evaluable patients with exclusively high-grade cancers. The authors defined high risk as serous, clear cell, carcinosarcoma and FIGO (International Federation of Gynecology and Obstetrics) grade 3 endometrioid histology, patients with biopsy-proven cervical involvement or deeply invasive (on imaging) grade 1 or 2 disease.…”
Section: Sln Biopsy For High-grade Cancersmentioning
confidence: 99%